PENGARUH KETERSEDIAAN MEDIA AUDIO VISUAL TERHADAP KEAKTIFAN BELAJAR PPKn SISWA KELAS VIII SMP NEGERI 2 BANGOREJO BANYUWANGI - harjianto, Harjianto (JPK (Jurnal Pancasila dan Kewarganegaraan), 2017)
This research aimed to measure the effect of the availability of audio-visual media to the 8th grade students’ learning citizenship education activeness SMPN 2 Bangorejo Banyuwangi. This type of research included a quantitative research design Ex-Post-Facto. In determining the respondents the researchers used proportional random sampling method with the number of respondents 50 students. This research uses simple linear regression analysis of the predictor. To determine the effect of independent variables on the dependent variables, can be seen on the probability of the inefficiency of the regression analysis. The analysis is done with the help of the SPSS program. Output of this research known that the value of t=3.858 with the significant value 0,000 < 0,05, Ho rejected and H1 accepted which means there is a real effect (significant) of visual media availability to the students’ learning activeness. The influence of the availability of audio visual media to the students’ learning activeness is 23.7%. This means that there is impact on availability of audio-visual media to 8th grade students’ learning activeness SMPN 2 Bangorejo Banyuwangi.